Statistical Evaluation of the Role of GNSS Signal Propagation Orientation in Low-Latitude Amplitude Scintillation Severity - Moraes, Alison; Sousasantos, Jonas; Affonso, Bruno J.; Silva, Paulo R. P.; De Paula, Eurico R.; Monico, Joao F. G. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Equatorial plasma bubbles are depleted plasma structures aligned to the geomagnetic field lines that are generated in the nighttime ionosphere bottomside and rise to the topside extending to increasingly higher latitudes. These structures induce fluctuations in the transionospheric radio signals causing the phenomenon known as ionospheric scintillation. Ionospheric scintillation is one of the main concerns for safety critical applications that rely on Global Navigation Satellite System information, therefore, the understanding about the occurrence and severity of scintillation is necessary. In this work, an analysis considering aspects of the orientation of the propagation of the radio signals through the plasma bubbles structures is performed to evaluate how this geometry can affect the scintillation profile. The dataset covers five months of records from three stations over the Brazilian region during the last solar cycle maximum. The initial results indicate that propagation paths fully aligned are consistently related to larger values of S4 and more severe scintillation. The statistical evaluations with the α - μ model show that during such cases stronger fading events are expected. According to the field measurements, fading events deeper than -15 dB are 73% more likely to occur under some aligned environments when compared to other propagation paths.
Keywords: Alpha-mu distribution; equatorial plasma bubbles; fading coefficients; GNSS propagation orientation